Farmer-preferred traits and variety choices for finger millet in Uganda - Hamba, Sophia; Kasule, Faizo; Mayanja, Ibrahim; Biruma, Moses; Natabirwa, Hedwig; Sanya, Losira Nasirumbi; Rubin, Deborah; Occelli, Martina; Adikini, Scovia (Frontiers in Sustainable Food Systems, 2024)
Finger millet is a climate-resilient crop providing food and nutrition security and income to millions of Ugandans. The current productivity of finger millet in farmers' fields is low due to poor adoption of improved varieties by farmers among other factors. This study was conducted to identify and profile varietal traits desired by finger millet farmers and consumers and how these traits vary among women and men in the finger millet value chain. Data were collected using semi-structured questionnaires from 173 households growing millet, 11 focus group discussions, and 3 key informant interviews from Bushenyi, Lira, and Nwoya districts. Data were analyzed using descriptive statistics, t-test, principal component analysis, and probit regression model. The majority of the farmers (97%) prefer growing landrace varieties of finger millet compared to only 3% growing improved varieties. The most preferred varieties were Kaguma in Bushennyi, Ajuko Manyige in Nwoya, Kal Atar, and Okello Chiba in Lira. Farmers' choice of variety depends on a combination of traits including agronomic, marketing, and consumption traits. The most preferred traits across regions were early maturity, high yield, drought tolerance, taste, big head, high market demand, disease resistance, big grain size, pest tolerance, and medium plant height, and these varied among women and men. Consumption traits such as taste, color, and good cooking quality were key factors in determining the adoption of new millet varieties. Gender, marital status, education levels, and occupation are the major socio-demographic factors that influence specific preferences related to finger millet variety. This study lays a foundation for designing a gender-responsive finger millet product profile to guide the development and release of new varieties by the finger millet Crop Improvement Program.